Effective Strategies for Optimal Implementation of Evolution and Innovation Packages in Medical Education - Hmid Reza Arasteh; Razieh Ghorbandoost; Hossein Abasian; Hsanreza Zin abadi (Babol University of Medical Sciences, 2020)
ABSTRACT BACKGROUND AND OBJECTIVE: Evolution and innovation packages in medical science education are the main program of medical education and it is necessary to pay attention to the provision of infrastructure of their implementation. This study was conducted to identify effective strategies for optimal implementation of evolution and innovation packages in medical education. METHODS: The method used in this research is thematic analysis. In this study, all key informed individuals involved in the implementation of evolution and innovation packages in medical education were considered as the target population and the sampling was performed using bullet technique. Data were analyzed using Maxqda 10 software. Participatory review method and review of non-participating experts were used in order to obtain validity and reliability of data. FINDINGS: 9 main categories, namely implementation measures of evolution packages, measures at the structural level, policy measures, environmental measures, managerial measures, motivational measures, measures related to capabilities and occupation, measures in the field of culture, and measures in the area of leadership were identified according to the results of the qualitative study. CONCLUSION: Presenting effective strategies for the optimal implementation of evolution and innovation packages in universities can have positive consequences in the improvement of the quality of medical education. The most important issues for implementation include serious attention of the authorities to the implementation of the packages, the involvement of all university staff, and the management stability in the optimal implementation of the packages.